2014
DOI: 10.1021/sc500107q
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Surface Runoff Quality Using Modified Sorbents

Abstract: The objective of this study was to develop and test nanoparticle-and polymer-based bioactive amended sorbents to enhance stormwater runoff treatment in best management practices (BMPs). Red cedar wood and expanded shale were the sorbents tested. Red cedar wood chips (RC) were modified with 3-(trihydroxysilyl) propyldimethyloctadecyl ammonium chloride (TPA) and silver nanoparticles (AgNPs) at different mass loadings (0.36 mg/g, 0.67 mg/g, and 0.93 mg/g for TPA and 0.33 mg/g and 0.68 mg/g for AgNPs) to simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…Following the procedures described by Kasaraneni et al, the red cedar wood chips were amended with 6 mg/g 3-(trihydroxysilyl)propyldimethyloctadecyl ammonium chloride (TPA), a quaternary ammonium compound [29]. Briefly, the red cedar was soaked in frequently exchanged clean water for a minimum of 2 weeks to leach out soluble matter and remove fines.…”
Section: Itf Preparationmentioning
confidence: 99%
See 3 more Smart Citations
“…Following the procedures described by Kasaraneni et al, the red cedar wood chips were amended with 6 mg/g 3-(trihydroxysilyl)propyldimethyloctadecyl ammonium chloride (TPA), a quaternary ammonium compound [29]. Briefly, the red cedar was soaked in frequently exchanged clean water for a minimum of 2 weeks to leach out soluble matter and remove fines.…”
Section: Itf Preparationmentioning
confidence: 99%
“…The E. coli removal during the field experiment was similar for both the tree filters, i.e., 99.2% and 99.1% for CTF and ITF, respectively. Although from preliminary batch tests it was expected that the ITF will have higher bacteria removal than the CTF system [29].Subsequent laboratory column experiments showed that a loading of greater than 6 mg/g of TPA to red cedar is required (i.e., 9 mg/g) to achieve measurable inactivation of bacteria under dynamic conditions [15]. Even though similar E. coli removal rates were found in the tracer experiments, the data suggest that when clean water is pumped following the tracer injection the E. coli concentration in the effluent of the ITF decreased more readily compared to CTF (Figure 2).…”
Section: Field Tracer Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, vegetation with extensive root structures was shown to improve E. coli retention in stormwater biofilters [13]. Filter media modified with either antimicrobial compounds [14,15] or adsorption enhancements [16,17] were found to improve faecal indicator microorganism attenuation rates. Intermittent wetting/drying operation is generally associated with poor removal performances due to decreased microbial adsorption and increased microbial desorption [7,8,17].…”
Section: Introductionmentioning
confidence: 99%